Flaxseed secoisolariciresinol diglucoside (SDG) during lactation improves bone metabolism in offspring at adulthood - Mariana Sarto Figueiredo (Journal of Functional Foods, 2017)
Secoisolariciresinol diglucoside (SDG), flaxseed lignan, has estrogenic effects and since flaxseed causes several dysfunctions in adult offspring from mothers supplemented during lactation, we hypothesized that maternal exposure to SDG during lactation changes bone parameters on adult offspring. At birth, dams (4 male and 4 female pups/litter) were divided into: standard diet (control group) or a diet supplemented with SDG: 4 mg/100 g, 40 mg/100 g or 400 mg/100 g groups. After weaning, all pups received a standard diet. At PN180, male 4SDG presented higher body fat mass with no changes were found in females. Males 40SDG presented higher spine bone mineral density (BMD), total bone mineral content (BMC) and bone area at PN180. Female 4SDG and 40SDG showed higher total and spine BMD, while only female 40SDG showed higher total BMC at PN180. Thus, neonatal exposure to intermediary dose of SDG results in denser bones at adulthood, suggesting that dietary SDG may potentially benefit bone development.